Che - Palmer, Dean; Palmer, Dean; Arnstein, Simon; Arnstein, Simon (Channel Four Television Corporation, 1996)
Resumen: Presenta la biografía del político, militar, escritor, periodista y médico Ernesto "Che" Guevara.